1992
DOI: 10.1007/bf01309594
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne encephalitis virus interaction with the target cells

Abstract: The binding of tick-borne encephalitis virus to porcine kidney embryo cells was studied. Anti-idiotypic antibodies against TBE virus E protein precipitated gp110 kDa which is predicted to be a cellular receptor for TBE virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…There are two major receptor candidates for TBEV in mammalian cells, laminin-binding protein (LBP) and the αVβ3 integrin but no receptor candidates in tick cells have been identified so far [ 61 , 62 , 63 ]. Studies using anti-idiotypic antibodies suggested that there could be other receptor candidates of as yet unknown identity [ 61 , 64 , 65 ]. In addition, under certain conditions it is possible to fuse TBEV with liposomes, hence, lipids could also be involved in binding [ 66 , 67 ].…”
Section: Life Cyclementioning
confidence: 99%
“…There are two major receptor candidates for TBEV in mammalian cells, laminin-binding protein (LBP) and the αVβ3 integrin but no receptor candidates in tick cells have been identified so far [ 61 , 62 , 63 ]. Studies using anti-idiotypic antibodies suggested that there could be other receptor candidates of as yet unknown identity [ 61 , 64 , 65 ]. In addition, under certain conditions it is possible to fuse TBEV with liposomes, hence, lipids could also be involved in binding [ 66 , 67 ].…”
Section: Life Cyclementioning
confidence: 99%
“…Most flaviviruses replicate in vertebrate and arthropod cells and exhibit a wide species and tissue tropism. Numerous candidate receptor proteins with a molecular mass of 40 to 80 kDa have been found to associate with flaviviruses in binding assays (19,22,27,36,44). Furthermore, an important role of heparan sulfate has also been demonstrated for the attachment of dengue-2 virus to vertebrate cells (7).…”
mentioning
confidence: 99%
“…The direct relation between the number of virus receptor molecules and the susceptibility to Sindbis virus infection has been shown on BHK cells transfected with the high affinity laminin receptor gene [17]. Only one paper reports the identification of TBE virus receptor using anti-ID antibodies [35]. By trypsin treatment of virus-susceptible cells, the authors showed that at least one of the putative cellular receptors for TBE virus includes a protein component.…”
Section: Discussionmentioning
confidence: 99%